PERSPEKTIF ALKITAB TERHADAP KELUARGA KRISTEN - Hardi Budiyana (Program Studi Pendidikan Agama Kristen, 2018)
The concept of family comes from God. God confirmed the family with eternal purpose. The family is confirmed to create a community that is centered on God and creates relationships with God and others. Through the divine family God's plan is revealed. Abstrak: Konsep keluarga berasal dari Allah. Allah mengukuhkan keluarga dengan tujuan kekal. Keluarga dikukuhkan untuk mewujudkan persekutuan yang berpusat pada Allah dan menciptakan hubungan dengan Allah dan sesama. Melalui keluarga ilahi rencana Allah dinyatakan.